Foreign rule?: transnational, national, and local perspectives on Venice and Venetia within the “multinational” empire - Laven, David; Parker, Laura (Cambridge University Press, 2014)
The history of the Habsburg Empire in the post-Napoleonic era is frequently approached from the perspective of its various component nationalities. These were traditionally portrayed in the historiography as engaged in more-or-less open struggle with control from Vienna. This article argues that the over-privileging of such national categories can distort the picture. By looking at a number of case studies – the naming of Lombardy-Venetia, the Biblioteca italiana, the Panteon veneto – the relationship between Venice (and its Terraferma) and Habsburg rule during the second Austrian domination is examined. It will be argued that it is more profitable to see Venetian identities (municipal, local, Italian, and as part of a wider transnational European culture) as capable of working for as well as against the empire, and that Habsburg policy was as often concerned with managing potential local rivalries (notably between Lombards and Venetians) as with controlling a perceived Italian threat. It is also suggested that, while cultivation of local identity was often used to reinforce the national, the Austrian authorities were also happy to annex both to further imperial interests.